Des tranchées au NSDAP. Culture de guerre et politisation des députés nazis - Nicolas Patin (Amnis)
What was the main reason for German people to join the Nazi Party? In historical literature, First World War has been often depicted as a major explanation: the conflict is supposed to have created a “war culture” that would have led to the political mobilization of many Nazis. An analyze of the national-socialist members of the Reichstag between 1919 and 1933 does not contradict this hypothesis. Indeed, 80% of NSDAP MP’s were war veterans. Nevertheless, in other parties too, an enormous proportion of delegates were veterans. Actually other particularities can be identified among Nazi members of the Parliament. The combination of these factors with war experience can give a more thorough and realistic picture. Therefore NSDAP had not the monopoly of war experience, but the one of youth and war experience. The Nazi MP’s were ten years younger than the other fractions of the Parliament. Moreover, a higher part of them were career soldiers, and soldiers’sons. They were also more attached to the countryside, by birth, profession their fathers’professions or the subjects they decided to study. All these criteria lead to question the usual excessive focus on War experience. Much more complex was the Nazi political commitment.